2019
DOI: 10.3390/nu11071664
|View full text |Cite
|
Sign up to set email alerts
|

Lipotoxicity in Kidney, Heart, and Skeletal Muscle Dysfunction

Abstract: Dyslipidemia is a common nutritional and metabolic disorder in patients with chronic kidney disease. Accumulating evidence supports the hypothesis that prolonged metabolic imbalance of lipids leads to ectopic fat distribution in the peripheral organs (lipotoxicity), including the kidney, heart, and skeletal muscle, which accelerates peripheral inflammation and afflictions. Thus, lipotoxicity may partly explain progression of renal dysfunction and even extrarenal complications, including renal anemia, heart fai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
105
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(109 citation statements)
references
References 134 publications
3
105
0
1
Order By: Relevance
“…It was reported that a long-term high-fat / sucrose diet promoted lipid deposition, glomerular hypertrophy, and apoptosis in the kidney. 3,41 In this study, a similar HFD induced pathological outcomes, including lipid deposition and hypertrophy in the renal glomerulus areas, as well as fibrosis in the renal cortex and outer medulla ( Fig. 2(b) and (d)).…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…It was reported that a long-term high-fat / sucrose diet promoted lipid deposition, glomerular hypertrophy, and apoptosis in the kidney. 3,41 In this study, a similar HFD induced pathological outcomes, including lipid deposition and hypertrophy in the renal glomerulus areas, as well as fibrosis in the renal cortex and outer medulla ( Fig. 2(b) and (d)).…”
Section: Discussionsupporting
confidence: 58%
“…Cardiovascular disease was also strongly associated with renal function because the kidney might directly influence the total blood volume and blood pressure. It was reported that a long‐term high‐fat / sucrose diet promoted lipid deposition, glomerular hypertrophy, and apoptosis in the kidney . In this study, a similar HFD induced pathological outcomes, including lipid deposition and hypertrophy in the renal glomerulus areas, as well as fibrosis in the renal cortex and outer medulla (Fig.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…Adipocytes act as fuel tanks for the storage of lipids and triglycerides. However, in non-adipocytes, which have a limited capacity to metabolize excessive lipids, their accumulation (steatosis) alter homeostasis and promote cell dysfunction [4].…”
Section: Introductionmentioning
confidence: 99%